2019
DOI: 10.1186/s40169-019-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Sites of synchronous distant metastases and prognosis in prostate cancer patients with bone metastases at initial diagnosis: a population‐based study of 16,643 patients

Abstract: BackgroundBone is a preferential site for prostate cancer (PCa) metastasis. However, sites of synchronous distant metastases in PCa patients with bone metastases at initial diagnosis and their impacts on prognosis are still unclear, limiting our ability to better stratify and treat the patients. In this study, we examined the sites of synchronous extra‐skeletal metastases in de novo PCa patients with bone metastases and their associated prognoses. MethodsIn total, 16,643 de novo PCa patients with bone metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…In our study, approximately 60% of patients were male, which agrees with previous studies [11,17,18]. Marital status has been increasingly recognized as an important factor in the survival of cancer patients [19]. In our study, most patients were married (58.3%), and we found that being married was associated with better patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, approximately 60% of patients were male, which agrees with previous studies [11,17,18]. Marital status has been increasingly recognized as an important factor in the survival of cancer patients [19]. In our study, most patients were married (58.3%), and we found that being married was associated with better patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…According to our results, the mean age of patients with mucinous PCa at diagnosis was 62.77 years, which agrees with Samaratung et al's reports of an average age of 61.4 years (9). Our study demonstrated that older age (age > 65 years) was associated with worse prognosis, which is consistent with previous reports of typical PCa (11,12). Our study may contribute to the prognosis prediction for this rare histological variant of PCa.…”
Section: Older Age At Diagnosis Was Associated With Poor Survivalsupporting
confidence: 92%
“…The nomogram is a statistics-based tool that calculates the probability of clinical events by considering the preweight value of each factor 12,13 . In recent years, nomograms have been widely used to predict the survival rate of various cancers 11,14,15 .…”
mentioning
confidence: 99%